(untitled) (Romanian Biotechnological Letters, 2024)
Detecting healthcare-associated infections (HAIs) is crucial as HAIs can pose a significant threat to patient safety, particularly among vulnerable populations such as the elderly, immunocompromised individuals, and those undergoing invasive medical procedures. Also, it is important to monitor the effectiveness of antibiotics and identify the resistance patterns of microorganisms to ensure appropriate treatment options. Bacteriology external quality control programs provide a means for laboratories to assess their performance and identify areas that require improvement. By participating in such programs, laboratories can evaluate their procedures, equipment, and personnel to ensure that they are producing reliable and accurate results because the External Quality Control (EQC) programs are carried out by medical laboratories using identical procedures as those used for handling patient samples. Our investigation centered on the performance of Romanian Public Health Units in identifying bacteria and conducting antimicrobial susceptibility testing in Bacteriology EQC programs associated with some of the most prevalent HAIs, such as blood infections, respiratory infections, and postoperative infections.